Oral Water Has Cardiovascular Effects Up to 60 min in Shock Patients - Guinot, Pierre-Grégoire; Nguyen, Maxime; Duclos, Valerian; Berthoud, Vivien; Bouhemad, Belaid; , The water study group; Radhouani, Mohamed; Constandache, Tiberiu; Grosjean, Sandrine; Bar, Pierre-Alain; Voizeux, Pierre; Rafrafi, Emel; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aim: Little is known about the cardiovascular effects of oral water intake in shock patients. This study was designed to assess the effect of oral water on stroke volume and blood pressure during a 1-h time period. Method and Results: This open-label, randomized clinical trial included patients admitted to intensive care with acute circulatory failure. Three ICU units at the anesthesia and critical care department of the Dijon Bourgogne University Hospital. Patients were randomized 1:1 to an intervention or standard care group. The intervention group received 500 ml of oral water while the standard care group received intravenous administration of 500 ml of physiological saline solution. Baseline SV did not differ between the two groups (36 ml [28;51] vs. 38 ml [30;51], p = 0.952). The number of patients who were fluid responders did not differ between the two groups [n = 19 (76%) vs. n = 18 (72%), p = 1]. The median change in stroke volume during the three time points did not differ between the two groups (p < 0.05). In the intervention group, blood pressure increased up to 60 min. In the control group, blood pressure quickly increased at the end of fluid expansion, then returned close to baseline value at 60 min. Conclusion: Shock patients who were administered oral water experienced improvements in blood pressure and blood flow up to 60 min when compared with patients who received intravenous saline solution. Further studies are warranted to confirm these effects. Clinical Trial Registration:www.clinicaltrials.gov, identifier: NCT03951519.